Molecular Ultrasound Imaging of αvβ3-Integrin Expression in Carotid Arteries of Pigs After Vessel Injury. Issue 12 (December 2016) - Rix, Anne; Fokong, Stanley; Heringer, Sarah; Pjontek, Rastislav; Kabelitz, Lisa; Theek, Benjamin; Brockmann, Marc-Alexander; Wiesmann, Martin; Kiessling, Fabian
Abstract : Objectives: Interventions such as balloon angioplasty can cause vascular injury leading to platelet activation, thrombus formation, and inflammatory response. This induces vascular smooth muscle cell activation and subsequent re-endothelialization with expression of αv β3 -integrin by endothelial cells and vascular smooth muscle cell. Thus, poly- N -butylcyanoacrylate microbubbles (MBs) targeted to αv β3 -integrin were evaluated for monitoring vascular healing after vessel injury in pigs using molecular ultrasound imaging. Materials and Methods: Approval for animal experiments was obtained. The binding specificity of αv β3 -integrin–targeted MB to human umbilical vein endothelial cells was tested with fluorescence microscopy. In vivo imaging was performed using a clinical ultrasound system and an 8-MHz probe. Six mini pigs were examined after vessel injury in the left carotid artery. The right carotid served as control. Uncoated MB, cDRG-coated MB, and αv β3 -integrin–specific cRGD-coated MB were injected sequentially. Bound MBs were assessed 8 minutes after injection using ultrasound replenishment analysis. Measurements were performed 2 hours, 1 and 5 weeks, and 3 and 6 months after injury. In vivo data were validated by immunohistochemistry. Results: Significantly stronger binding of cRGD-MB than MB and cDRG-MB to human umbilical vein endothelial cells was found ( P < 0.01). As vessel injury leads to upregulation of αv β3 -integrin, cRGD-MBs bound significantly stronger ( P < 0.05) in injured carotid arteries than at the counter side 1 week after vessel injury and significant differences could also be observed after 5 weeks. After 3 months, αv β3 -integrin expression decreased to baseline and binding of cRGD-MB was comparable in both vessels. Values remained at baseline also after 6 months. Conclusions: Ultrasound imaging with RGD-MB is promising for monitoring vascular healing after vessel injury. This may open new perspectives to assess vascular damage after radiological interventions.